(untitled) (Bangladesh Journal of Pharmacology, 2015)
Viola odorata is traditionally used in the management of gastrointestinal, respiratory and vascular disorders. The present study was undertaken to validate its folkloric uses. The application of V. odorata to spontaneous contractions in isolated rabbit jejunum preparation exerted relaxant effect through decrease in magnitude and frequency of contractions. Moreover, it also caused relaxation of K+ (80 mM)-induced contractions and shifted the Ca2+ concentration response curves toward right in isolated jejunum similar to verapamil (standard Ca2+ channel blocker), confirming Ca2+ channel blocking activity. V. odorata also caused relaxation of carbachol (1 µM)- and K+ (80 mM)-induced contractions in isolated rabbit tracheal preparations comparable to verapamil, reflecting that observed relaxant effect may be the outcome of anti-muscarinic and/or Ca2+ channel blocking activities. It also exerted relaxant effect on phenylephrine (1 µM)- and K+ (80 mM)-induced contractions in isolated rabbit aortic preparations thus providing rationale for its folkloric uses to treat diarrhea, asthma and hypertension.